Δ12-Fatty acid desaturase from Candida parapsilosis is a multifunctional desaturase producing a range of polyunsaturated and hydroxylated fatty acids - Buček, Aleš; Matoušková, Petra; Sychrová, Hana; Pichová, Iva; Hrušková-Heidingsfeldová, Olga (PloS one, 2014)
Numerous Δ12-, Δ15- and multifunctional membrane fatty acid desaturases (FADs) have been identified in fungi, revealing great variability in the enzymatic specificities of FADs involved in biosynthesis of polyunsaturated fatty acids (PUFAs). Here, we report gene isolation and characterization of novel Δ12/Δ15- and Δ15-FADs named CpFad2 and CpFad3, respectively, from the opportunistic pathogenic yeast Candida parapsilosis. Overexpression of CpFad3 in Saccharomyces cerevisiae strains supplemented with linoleic acid (Δ9,Δ12-18:2) and hexadecadienoic acid (Δ9,Δ12-16:2) leads to accumulation of Δ15-PUFAs, i.e., α-linolenic acid (Δ9,Δ12,Δ15-18:3) and hexadecatrienoic acid with an unusual terminal double bond (Δ9,Δ12,Δ15-16:3). CpFad2 produces a range of Δ12- and Δ15-PUFAs. The major products of CpFad2 are linoleic and hexadecadienoic acid (Δ9,Δ12-16:2), accompanied by α-linolenic acid and hexadecatrienoic acid (Δ9,Δ12,Δ15-16:3). Using GC/MS analysis of trimethylsilyl derivatives, we identified ricinoleic acid (12-hydroxy-9-octadecenoic acid) as an additional product of CpFad2. These results demonstrate that CpFAD2 is a multifunctional FAD and indicate that detailed analysis of fatty acid derivatives might uncover a range of enzymatic selectivities in other Δ12-FADs from budding yeasts (Ascomycota: Saccharomycotina).
Keywords: Saccharomyces cerevisiae; molekulární sekvence - údaje; sekvence aminokyselin; Amino Acid Sequence; Ricinoleic Acids; desaturasy mastných kyselin; Linoleic Acid; Fatty Acids, Unsaturated; Molecular Sequence Data; Phylogeny; nenasycené mastné kyseliny; kyseliny ricinolejové; fylogeneze; Fatty Acid Desaturases; kyselina linolová; Candida